Spectroscopic Investigations of Pentobarbital Interaction with Transthyretin - Saqer M. Darwish; Jafar Ghithan; Musa M. Abuteir; Mariam Faroun; Mahmoud M. Abu-hadid (Journal of Spectroscopy)
Transthyretin (TTR) aggregation has been characterized to be responsible for several amyloid diseases. Fourier transform infrared (FTIR) spectroscopy, fluorescence, and atomic force microscopy (AFM) are used to investigate secondary structure changes in transthyretin, induced upon thermal denaturation and interaction with pentobarbital. Spectral analysis revealed a strong static quenching of the intrinsic fluorescence of TTR by pentobarbital with a binding constant (K) estimated at 2.092×103 M-1. Fourier self-deconvolution (FSD) technique is used to evaluates intensity changes in the spectra of the component bands in the amide I and amide II regions due to the changes in pentobarbital concentration in the protein complex. The increases of the relative intensities of the peaks at 1614 cm−1 and 1507 cm−1 are due to the increase of pentobarbital concentrations which is linked to the formation of oligomers in the protein.